The mobile giving gap: The negative impact of smartphones on donation behavior - Hock, Stefan J.; Ferguson, Kristen A.; Herd, Kelly B. (Journal of Consumer Psychology, 2025)
AbstractWhile charities typically use the same messaging when appealing to consumers on their smartphones and PCs, this approach may backfire. Across three studies, we find consumers are less likely to donate on their smartphones (vs. PCs), a phenomenon we call the mobile giving gap. In study 1, we demonstrate that consumers are less willing to donate real money to a charitable organization. In study 2, we provide process support and demonstrate that the focal effect is mediated by other‐focus. Finally, a field experiment using Google display ads (study 3) replicates the focal effect and demonstrates that the negative impact of smartphones is attenuated when the appeal explicitly focuses on others (vs. the self). This study not only provides additional process support, but also suggests an easily implementable strategy that charities can use to close the mobile giving gap. Taken together, our findings offer theoretical insights related to the mobile mindset and its impact on consumer behavior and highlight that charities should tailor their donation appeals based on device type.